Dominant X linked subcortical laminar heterotopia and lissencephaly syndrome (XSCLH/LIS): evidence for the occurrence of mutation in males and mapping of a potential locus in Xq22. Issue 3 (March 1997) - des Portes, V; Pinard, J M; Smadja, D; Motte, J; Boespflüg-Tanguy, O; Moutard, M L; Desguerre, I; Billuart, P; Carrie, A; Bienvenu, T; Vinet, M C; Bachner, L; et al.
Abstract : X linked subcortical laminar heterotopia and lissencephaly syndrome (XSCLH/ LIS) is an intriguing disorder of cortical development, which causes classical lissencephaly with severe mental retardation and epilepsy in hemizygous males, and subcortical laminar heterotopia (SCLH) associated with milder mental retardation and epilepsy in heterozygous females. Here we report an exclusion mapping study carried out in three unrelated previously described families in which males are affected with lissencephaly and females with SCLH, using 38 microsatellite markers evenly distributed on the X chromosome. Most of the X chromosome was excluded and potential intervals of assignment in Xq22.3-q23 or in Xq27 are reported. Although the number of informative meioses did not allow a decision between these two loci, it is worth noting that the former interval is compatible with the mapping of a breakpoint involved in a de novo X;autosomal balanced translocation 46, XX, t(X;2)(q22;p25) previously described in a female with classical lissencephaly. In addition, haplotype inheritance in two families showed a grandpaternal origin of the mutation and suggested in one family the presence of mosaicism in germline cells of normal transmitting males.